2020
DOI: 10.1371/journal.ppat.1008868
|View full text |Cite
|
Sign up to set email alerts
|

Mining for humoral correlates of HIV control and latent reservoir size

Abstract: While antiretroviral therapy (ART) has effectively revolutionized HIV care, the virus is never fully eliminated. Instead, immune dysfunction, driven by persistent non-specific immune activation, ensues and progressively leads to premature immunologic aging. Current biomarkers monitoring immunologic changes encompass generic inflammatory biomarkers, that may also change with other infections or disease states, precluding the antigen-specific monitoring of HIV-infection associated changes in disease. Given our g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…All assays correlate significantly (p < 0.001) across donors, confirming they are reproducible and not biased by differences in FcR alleles or expression patterns. The observed significant correlations across technical replicates are in agreement with similar assays used by us in a range of other contexts, 10,29,30,51 as well as in several technical benchmarks. 47,50,52 Antibody isotype and subclass analysis The isotypes and subclasses of malaria antigen-specific antibodies were quantified using a previously described method.…”
Section: Technical Replication Of Cell-based Assays Across Primary Innate Immune Cell Donorssupporting
confidence: 87%
See 1 more Smart Citation
“…All assays correlate significantly (p < 0.001) across donors, confirming they are reproducible and not biased by differences in FcR alleles or expression patterns. The observed significant correlations across technical replicates are in agreement with similar assays used by us in a range of other contexts, 10,29,30,51 as well as in several technical benchmarks. 47,50,52 Antibody isotype and subclass analysis The isotypes and subclasses of malaria antigen-specific antibodies were quantified using a previously described method.…”
Section: Technical Replication Of Cell-based Assays Across Primary Innate Immune Cell Donorssupporting
confidence: 87%
“…To further explore the specific differences in humoral immune profiles between the RRR and RRr regimens, we used a least absolute shrinkage and selection operator (LASSO)-based modeling approach, 10,29,30 which helps to prevent overfitting in high-dimensional datasets (i.e., a dataset with more antibody measurements than subjects). 31 We identified just four antibody features that could accurately discriminate between the vaccine groups (Figures 1C-1E).…”
Section: Resultsmentioning
confidence: 99%
“…The predictive performance of all methods was evaluated in a stringent leave-one-out cross-validation (LOOCV) framework (Methods). We have previously demonstrated that on such multi-omic datasets, cross-validation is a gold standard to evaluate model performance with data held out 5, 6, 8 . In a LOOCV framework, we found that PFR had no predictive power (AUC < 0.5), while LASSO and PLS had weak predictive power in predicting age as a categorical variable (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Existing analytical approaches have primarily focused on individual "omic" datasets with relatively few attempts at integration of multi-omic datasets. In either case, we [5][6][7][8][9] and others [10][11][12] have primarily emphasized on uncovering predictive biomarkers (Fig. 1a).…”
Section: Introductionmentioning
confidence: 94%
“…whether humoral biomarkers of reservoir size can estimate the reservoir size in ART-treated subjects, and they observed that IgG-gp41 (r=0.597, p=0.011) and IgG3-gp120 (r=0.135, p=0.029) HIV-specific antibodies correlate with the size of the HIV reservoir in these subjects (99).…”
Section: Relationship Between Hiv-1-specific Antibodies and Hiv-1 Dnamentioning
confidence: 99%